Shattering the Amyloid Illusion: The Microbial Enigma of Alzheimer’s Disease Pathogenesis—From Gut Microbiota and Viruses to Brain Biofilms - Anna Onisiforou; Eleftheria G. Charalambous; Panos Zanos (Microorganisms)
For decades, Alzheimer’s Disease (AD) research has focused on the amyloid cascade hypothesis, which identifies amyloid-beta (Aβ) as the primary driver of the disease. However, the consistent failure of Aβ-targeted therapies to demonstrate efficacy, coupled with significant safety concerns, underscores the need to rethink our approach to AD treatment. Emerging evidence points to microbial infections as environmental factors in AD pathoetiology. Although a definitive causal link remains unestablished, the collective evidence is compelling. This review explores unconventional perspectives and emerging paradigms regarding microbial involvement in AD pathogenesis, emphasizing the gut–brain axis, brain biofilms, the oral microbiome, and viral infections. Transgenic mouse models show that gut microbiota dysregulation precedes brain Aβ accumulation, emphasizing gut–brain signaling pathways. Viral infections like Herpes Simplex Virus Type 1 (HSV-1) and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) may lead to AD by modulating host processes like the immune system. Aβ peptide’s antimicrobial function as a response to microbial infection might inadvertently promote AD. We discuss potential microbiome-based therapies as promising strategies for managing and potentially preventing AD progression. Fecal microbiota transplantation (FMT) restores gut microbial balance, reduces Aβ accumulation, and improves cognition in preclinical models. Probiotics and prebiotics reduce neuroinflammation and Aβ plaques, while antiviral therapies targeting HSV-1 and vaccines like the shingles vaccine show potential to mitigate AD pathology. Developing effective treatments requires standardized methods to identify and measure microbial infections in AD patients, enabling personalized therapies that address individual microbial contributions to AD pathogenesis. Further research is needed to clarify the interactions between microbes and Aβ, explore bacterial and viral interplay, and understand their broader effects on host processes to translate these insights into clinical interventions.